GNS561 acts as a potent anti-fibrotic and pro-fibrolytic agent in liver fibrosis through TGF-β1 inhibition. (July 2020) - Bestion, Eloïne; Jilkova, Zuzana Macek; Mège, Jean-Louis; Novello, Marie; Kurma, Keerthi; Pour, Seyedeh Tayebeh Ahmad; Lalmanach, Gilles; Vanderlynden, Lise; Fizanne, Lionel; Bassissi, Firas; Rachid, Madani; Tracz, Jennifer; et al.
Background: Hepatic fibrosis is the result of chronic liver injury that can progress to cirrhosis and lead to liver failure. Nevertheless, there are no anti-fibrotic drugs licensed for human use. Here, we investigated the anti-fibrotic activity of GNS561, a new lysosomotropic molecule with high liver tropism. Methods: The anti-fibrotic effect of GNS561 was determined in vitro using LX-2 hepatic stellate cells (HSCs) and primary human HSCs by studying cell viability, activity of caspases 3/7, autophagic flux, cathepsin maturation and activity, HSC activation and transforming growth factor-β1 (TGF-β1) maturation and signaling. The contribution of GNS561 lysosomotropism to its anti-fibrotic activity was assessed by increasing lysosomal pH. The potency of GNS561 on fibrosis was evaluated in vivo in a rat model of diethylnitrosamine-induced liver fibrosis. Results: GNS561 significantly decreased cell viability and promoted apoptosis. Disrupting the lysosomal pH gradient impaired its pharmacological effects, suggesting that GNS561 lysosomotropism mediated cell death. GNS561 impaired cathepsin activity, leading to defective TGF-β1 maturation and autophagic processes. Moreover, GNS561 decreased HSC activation and extracellular matrix deposition by downregulating TGF-β1/Smad and mitogen-activated proteine kinase signaling and inducing fibrolysis. Finally, oral administration of GNS561 (15 mg/kg per day) was well tolerated and attenuated diethylnitrosamine-induced liver fibrosis in this rat model (decrease of collagen deposition and of pro-fibrotic markers and increase of fibrolysis). Conclusion: GNS561 is a new potent lysosomotropic compound that could represent a valid medicinal option for hepatic fibrosis treatment through both its anti-fibrotic and its pro-fibrolytic effects. In addition, this study provides a rationale for targeting lysosomes as a promising therapeutic strategy in liver fibrosis.